EFEKTIVITAS PELAKSANA KEGIATAN SL-PTT PADI SAWAH DI PROVINSI BANTEN - Kartono Kartono; Eko Sri Mulyani; Kardiono Kardiono; Asih Mulyaningsih; Hari Soesanto; Iin Setyowati; Retno Umiarsih; Pipit Apifah (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2015)
Effectiveness of SL-PTT activity requires dynamic creativity in concocting the use of various methodsof learning appropriate. Effectiveness is the relationship between the objectives and results to beachieved, as the effects caused by their activities. The purpose of this study wanted to clarify theeffectiveness of the activities of rice based SL-PTT on the increase in the competencies (knowledge,skills and attitudes) learning objectives (farmers) in the province of Banten. Location of the studyconducted in four districts in Banten province, namely : Serang, Pandeglang, Lebak and Tangerang.respondents and the research informants purposively determined in accordance with the problems andresearch objectives. Data collection through focus group discussions and interviews. Data wereanalyzed by descriptive analytical to explain the effectiveness of SL-PTT activity as measured by theparameters level of knowledge, skills and attitude of the respondent farmers. The level of learningeffectiveness SL-PTT rice in Banten province there is a gap between the level of competence of thefarmer participants and non participants SL-PTT rice.